Electronic resource management in libraries research and practice - Yu, Holly; Breivold, Scott (Information Science Reference, 2008)
"This book provides comprehensive coverage of the issues, methods, theories, and challenges connected with the provision of electronic resources in libraries, with emphasis on strategic planning, operational guidelines, and practices. Its primary focus is management practices of the life-cycle of commercially acquired electronic resources from selection and ordering to cataloging, Web presentation, user support, usage evaluation, and more"--Provided by publisher.